EMPLOYEE RETENTION STRATEGIES IN THE DIGITAL ERA IN PRIVATE RETAIL COMPANIES IN WEST JAVA - Darliani Nurulita; Farida Yuliaty (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze and empirically test the simultaneous and partial effects of Digital Training, Transformational Leadership, and Workplace Well-being on Employee Retention in a private retail company amidst the massive digital transformation. The high rate of employee turnover in the retail sector requires a retention strategy that is adaptive to the demands of technology and the modern workforce. This quantitative study uses a causal approach. Data were collected through distributing questionnaires to 75 employee respondents of PT Retail Nusantara, then analyzed using Multiple Linear Regression analysis. The results show that Digital Training, Transformational Leadership, and Workplace Well-being simultaneously have a significant effect on Employee Retention (F_{count}=42.781, Sig. 0.000). Partially, Digital Training (t=4.875) is proven to be the variable with the most dominant influence, followed by Transformational Leadership and Workplace Well-being. The coefficient of determination shows the contribution of the three variables is 68.2% to employee retention. This study provides critical empirical evidence for HR management that in the digital era, investing in improving employees' technological competencies through Digital Training programs is the most effective retention strategy, which must be integrated with a supportive leadership style and policies that ensure work-life balance.